Commons and Bio-Cultural Learning: An Environmental Humanities View on Evolution, Materiality and Society - Majo, Claudio de (Fronteira: Journal of Social, Technological and Environmental Science, 2022)
This article aims to critically contribute to contemporary commons scholarship, using the lenses of the environmental humanities. Linking existing literature on collective action to a vast amount of literature from both the social sciences and the natural sciences could contribute to a new epistemological framework to understand anthropogenic processes of collective action. Both recent biological evolution theories and ontologically oriented philosophical perspectives have insisted on the endemic collaborative nature of coexistence processes as the embodiment of a larger ecological, material, and cultural whole. Looking at these processes through the lenses of coexistence could potentially reshape commons scholarship, overcoming what I define as the â€œlong shadow of Hardinism,â€ while simultaneously further stimulating dialogue, and hopefully consilience, between the social and natural sciences.